The use and abuse of cinema : German legacies from the Weimar era to the present - Rentschler, Eric (Film and culture., 2015)
Eric Rentschler explores the screen fantasies and spectacles that derive from Germany's fraught modern experience and follows the traces of these sights and sounds to the postmillenial present. Each chapters contains a stirring minidrama, discussing prominent critics and theorists such as Siegfried Kracauer and Rudolf Arnheim; key New German directors such as Rainer Werner Fassbinder and Alexander Kluge; films from the so-called Berlin School, particularly those of Christoph Hochhäusler, Thomas Arslan, and Christian Petzold; and seminal genres such as the mountain film, the early sound musical.